FEAR OF MISSING OUT CONSTRUCTS NARCISSISM IN PAULA HAWKINS’ THE GIRL ON THE TRAIN - Kenrinus, Jepli; Margawati, Prayudias (Lire Journal (Journal of Linguistics and Literature), 2024)
Fear of Missing Out (FoMO) is related to society nowadays and can lead to narcissism. Therefore, this research objective was to analyze how FoMO constructs narcissism in Paula Hawkins’ The Girl on The Train through three major characters, including Rachel Watson, Megan Hipwell, and Anna Watson. The research was done by applying the FoMO process, the FoMO scale, and Freud’s psychoanalytic theory to answer the research objective. The research method was qualitative, in which data was written in the text, and researchers became the research instrument to gather primary data and second data. Primary data for this research was taken from Hawkins’ The Girl on the Train, consisting of words, utterances, and quotations. Meanwhile, secondary data sources were obtained from e-books, journals, and articles. Through this research, it was found that the major characters suffer from social and news FoMO, indicated by the perception of missing out and compulsive behavior in maintaining those social connections. Further, the FoMO indirectly construct their narcissism, which is characterized by megalomania, self-love, and personality.